Peran Mediasi Kepuasan Konsumen Pada Hubungan Kualitas Pelayanan dengan Niat Membeli Kembali Tamu Hotel di Kawasan Wisata Tanjung Benoa, Bali - Muhamad Hasbi; I Putu Utama (Pusat Penelitian & Pengabdian kepada Masyarakat, Politeknik Pariwisata Bali, 2022)
This research is aiming to determine the mediation role of consumer satisfaction in the relationship between service quality and repurchase intentions from hotel guests in the tourism area of Tanjung Benoa, Bali. The decline in the level of repeater guests at hotels created a gap in expectations from the hotel management. Data were collected using a questionnaire with 100 hotel guests as respondents. Hypothesis were tested using structural equation model (SEM) of SmartPLS. This study concluded that 1) service quality had a positive not significant relationship toward repurchase intentions, 2) customer satisfaction had a positive significant relationship toward consumer repurchase intentions, 3) service quality had a positive significant relationship toward consumer satisfaction and 4) customer satisfaction had a significant role in mediating (full mediation) relationship between service quality and repurchase intention. Referring to the result, it is recommended for the hotel management to more focus on the quality of services provided so that guests feel satisfied in the end create an intention to repurchase in the future. The challenges during this pandemic are also expected not to reduce the quality of the services at the same time also maintaining the guest satisfaction.